MAKNA PERUBAHAN LOGO PARTAI KEADILAN SEJAHTERA (PKS) DAN HUBUNGANNYA DENGAN BRAND IMAGE PKS - Muhammad, Ben Isa (Institut Bisnis dan Teknologi Indonesia, 2021)
Sunday, November 29, 2020, the Prosperous Justice Party (Partai Keadilan Sejahtera abbreviated as PKS) held their Fifth National Conference in Bandung and launched its new logo, march and hymn. The logo change is a value transformation proclaimed by PKS, which can be categorized as a company rebranding. This study used a qualitative approach with Charles Sanders Peirce's semiotic analysis. The authors tried to study and describe the meaning of the new PKS logo, and how the logo changes as part of the PKS rebranding. The research found that rebranding wise, this change is an evolutionary change, and the changes of the basic shapes and brand color from the dominant black-yellow colored box to the Orange-White colored circle and its meaning constitutes the most significant change, though philosophically, the party values remain maintained. The results concluded that the meaning represented in the PKS new visual logo was changing the image of the party from a more religious and formal one to a more neutral, youthful, fresh and dynamic. As part of the PKS's corporate rebranding, changing the logo is PKS strategy to attract new constituent, especially millennials. PKS has evolved its logo into a more modern, adaptive and organic design.